Een boecxken gemaket ende bescreven van suster Bertken die lvij iaren besloten heeft gheseten tot Utrecht in die buerkercke - Jacobsdochter, Berta 1426/7-1514 (Zwolle Tjeenk Willink, 1955)
Berta Jacobsdochter or Suster Bertken was a Dutch poet and anchorite. She was born the illegitimate daughter of the canon priest Jacob van Lichtenberg. Her life before her enclosure as an anchorite is unknown, but she was evidently given a good education. In 1456 or 1457, she let herself be enclosed in a cell as an anchorite at the Buurkerk in Utrecht with permission by Utrecht bishop David of Burgundy.According to a description of her life, she lived an extremely ascetic life even for an anchorite. After her death, several songs and hymns written by her were found among her belongings and were published in 1516. Her songs describe foremost her passion in the mystical union with God and became popular.Bertken lived in a small cell adjacent to the Buurkerk church of Utrecht for fifty-seven years until her death in 1514. Her daily activities were attending church from a window in her cell, meditation, prayer and writing. The only furniture in the cell was a chair, desk and mattress. Bertken never wore shoes and her diet excluded all dairy and meat products.
Originally published in 1516
Naar de eerste uitgave van Jan Berntsz. Utrecht 1516
Keywords: 15th Century (1401-1500); 16th Century (1501-1600); Monastery; Utrecht (Netherlands)